Flow visualization of water jet passing through the empty space of crossflow turbine runner - Sutikno, Djoko; Soenoko, Rudy; Wahyudi, Slamet; Soeparman, Sudjito (Eastern-European Journal of Enterprise Technologies, 2019)
Hydropower plants are a form of renewable energy resources, which comes from flowing water. The turbine is used to drive the generator then convert mechanical energy into electrical energy. The turbine wheel is located inside the turbine housing and the turbine wheel rotates the power shaft. One of the most used turbines is a cross-flow turbine. The pattern of water jet flowing throughout the empty space of the runner of the cross-flow turbine is influenced by the number of active runner blades pounded by water from the turbine nozzle. The difference in the flow patterns was believed having a relation to the performance differences of the three turbine models. The flow visualizations of water passing through the empty space of the cross-flow turbine runner were taken from the experimental study intended to investigate performance characteristics of three cross-flow turbine models designed on the same value of flow rates, runner diameters and rotational speeds; but each turbine model having different values of runner width as well as nozzle entry arc. Both of the nozzle and runner widths were designed as the function of the nozzle entry arc, therefore the shorter pair of runner-nozzle width the larger nozzle entry arc and vice versa. The flow visualizations of water passing on the turbine were studied using the empty space of the cross-flow turbine. The three models were tested on the same head and the same flow rate at the speed of 50, 100, 150, 250, 300 and 500 rpm. The photos of water flowing through the empty space in the turbine model runners were taken to find out the conditions of flow and the efficiency of the models was calculated to show the performance of the turbine. Images are taken within 10 cm and parallel to the turbine. The cross-flow turbine models were designed with 197 mm runner diameter of each and have the ratio of runner diameter to runner length of 1:2. One side of each turbine model end disk was made from transparent media named perspex facilitating the researcher to observe the water flow condition during flowing through inside the runner. The conditions of the flow of water passing through the empty space of turbine wheels were photographed using a Nikon camera equipped with a hallogen lamp having a power of 1000 watts to capture the difference of flow pattern among the three models of the turbine. The nozzle entry arcs used in this experimental study were 75o, 90o and 120o. In addition, the nozzle of each model has the same cross-sectional area and the roof of each was designed having roof curvature radius centered on the shaft axis. Such nozzle roof curvature was expected to be able to deliver water in the better direction as well as its flow condition as the water enters the turbine runner. The magnitude of the nozzle entry arc determines the number of active vanes pounded by the jet of water coming out of the nozzle, these conditions affect the pattern of water flow at the moment of passing through the empty space of the turbine wheel and then this flow pattern was believed to affect the performance characteristic of the cross-flow turbine. One side of each runner disk was made from Perspex, for the researcher to be able to observe the water flow condition during flowing through inside the runner.